Особливості укладання договору купівлі-продажу цінних паперів: теоретичний аспект - Самчук-Колодяжна, З.; Samchuk-Kolodyazhna, Z. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено теоретичні та практичні проблеми укладання договорів купівлі-продажу особливого виду майна – цінних паперів, які забезпечують оборотоспроможність такого майна. Оборотоздатність цінних паперів визначена на законодавчому рівні. Ступінь оборотоспроможності визначається як їх видом, так і способом легітимізації власника.The article focuses on the theoretical and practical problems of contract of sale special type of property – securities that provide reversible ability of such property. The reversible ability securities has determined according to the legislation. It is necessary to mark that the level of reversible ability is determined by the kind and method of legitimation owner and his status. The priority ia given to the professional participants of fund market and owners of documentary securities. A special interest is caused by the exchange transactions of relatively uncertificated securities, and legislative limitations of freedom of purchase-sale, corporate securities, taking into account control after producing and turn of emission securities. The legal nature of agreement of underwriting the subject of is emission securities documentary and uncertificated form of producing is the most debatable in scientific literature.
The Peculiarities of Purchase-sale Contract of Securities: Theoretical Aspect.
Keywords: оборотоспроможність; майнові права; цінні папери; reversible ability; property rights; securities